Spatial variability of microbial assemblages associated with a dominant habitat-forming seaweed - Campbell, Alexandra H.; Marzinelli, Ezequiel M.; Gelber, Jon; Steinberg, Peter D. (Frontiers in Microbiology, 2015)
Macroalgal surfaces support abundant and diverse microorganisms within biofilms, which are often involved in fundamental functions relating to the health and defence of their seaweed hosts, including algal development, facilitation of spore release and chemical antifouling. Given these intimate and important interactions, environmental changes have the potential to negatively impact macroalgae by disrupting seaweed-microbe interactions. We used the disappearance of the dominant canopy-forming fucoid Phyllospora comosa from the metropolitan coast of Sydney, Australia as a model system to study these interactions. We transplanted Phyllospora individuals from nearby, extant populations back onto reefs in Sydney to test whether bacterial assemblages associated with seaweed surfaces would be influenced by (i) the host itself, independently of where it occurs, (ii) the type of habitat where the host occurs or (iii) site-specific differences. Analyses of bacterial DNA fingerprints (TRFLPs) indicated that assemblages of bacteria on Phyllospora were not habitat-specific. Rather, they were primarily influenced by local, site-specific conditions with some evidence for host-specificity in some cases. This could suggest a lottery model of host-surface colonisation, by which hosts are colonised by ‘suitable’ bacteria available in the local species pool, resulting in high variability in assemblage structure across sites, but where some species in the community are specific to the host and possibly influenced by differences in host traits.